2017
DOI: 10.1021/acs.jpcc.6b10849
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Chemistry in Fluorinated Chemical Vapor Deposition of Silicon Carbide

Abstract: The use of chlorinated chemical vapor deposition (CVD) chemistry for growth of homoepitaxial layers of silicon carbide (SiC) has diminished the problem of homogenous gas phase nucleation, mainly the formation of Si droplets, in CVD of SiC by replacing Si-Si bonds with stronger Si-Cl bonds. Employing the even stronger Si-F bond could potentially lead to an even more efficient CVD chemistry, however, fluorinated chemistry is very poorly understood for SiC CVD. Here, we present studies of the poorly understood fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…These results also have significant implications to other industrial vapor deposition processes. For example, homogeneous nucleation of silicon and other semiconductors impedes the chemical vapor deposition (CVD) production of crystalline films (37), but the cleavage energy of bulk silicon (38) is around 1-2 J·m −2 , leading to a calculated 10 −16 -J barrier for homogeneous nucleation. This implies that nucleation should almost never occur, which is in contrast to experimental observations.…”
Section: Discussionmentioning
confidence: 99%
“…These results also have significant implications to other industrial vapor deposition processes. For example, homogeneous nucleation of silicon and other semiconductors impedes the chemical vapor deposition (CVD) production of crystalline films (37), but the cleavage energy of bulk silicon (38) is around 1-2 J·m −2 , leading to a calculated 10 −16 -J barrier for homogeneous nucleation. This implies that nucleation should almost never occur, which is in contrast to experimental observations.…”
Section: Discussionmentioning
confidence: 99%
“…From the starting position of the growth, the growth rate decreases slowly along the susceptor, giving rise to a slightly higher growth rate at certain positions as the C/Si ratio is increased. 15 It was ascribed to a changing effective C/Si ratio that decreased along the susceptor, i.e. higher effective C/Si ratio upstream and lower effective C/Si downstream.…”
Section: Discussionmentioning
confidence: 99%
“…17 In the fluorinated chemistry the Si species is not formed in high concentrations. 15 Together with the stable N2 molecule another reason for the increasing dopant incorporation along the gas flow can be that the kinetics of forming N dopant species is slow, thereby forming more such species downstream, creating a higher dopant concentration downstream.…”
Section: A N-type Doping Using N2mentioning
confidence: 99%
“…This is motivated by the low amounts of Si-C species found at thermodynamic equilibrium in the Si-C-H-F system. 8 Apart from H 2 , H and HF, 11 hydrocarbon species and 10 fluorosilanes were taken into account, plus SiH 4 , SiH 2 and Si. The full reaction scheme is listed in ESI, † Table S1.…”
Section: Modelingmentioning
confidence: 99%
“…SiC CVD using a fluorinated chemistry was first demonstrated in 2012 by Rana et al 7 Lately, it has been shown that a fluorinated chemistry, using SiF 4 and C 2 H 4 as precursors, renders a CVD chemistry that is very sensitive to the C/Si ratio of the growth species impinging the surface and with a deposition rate of only around 30 mm h À1 compared to 100 mm h À1 or more for a chlorinated or brominated chemistry. 8 We hypothesize that this behavior is due to the low reactivity of the SiF 4 molecule given its very strong Si-F bonds and the slower kinetics of the Si precursor, which is not matched to the faster kinetics of the C 2 H 4 precursor, rendering a less robust CVD chemistry, as manifested by the sensitivity to the impinging C/Si ratio. We test this hypothesis by kinetic modeling combined with experimental SiC deposition from SiF 4 and different hydrocarbons and show that the best-matched gas phase chemical kinetics renders the most robust SiC CVD.…”
Section: Introductionmentioning
confidence: 98%